Synthetic Carbons Derived from a Styrene—Divinylbenzene Copolymer Using Phosphoric Acid Activation - A.M. Puziy; O.I. Poddubnaya; A. Martínez-Alonso; F. Suárez-García; J.M.D. Tascón (Adsorption Science & Technology)
Activated carbons were obtained by phosphoric acid activation of a porous chloromethylated and sulphonated styrene—divinylbenzene copolymer in two different atmospheres (argon and air) at various temperatures in the range 400–1000°C. The development with activation temperature of several characteristic parameters of the resulting carbons, i.e. bulk density, yield, surface area, meso-, micro- and ultra-micropore volumes, and cation-exchange capacity, was examined. All these parameters were recalculated relative to the volume of adsorbent (to obtain their practical effectiveness) and then related to the same quantity of precursor (to yield their economic efficiency). It is concluded that the carbons obtained in an argon atmosphere exhibit some practical advantages over those obtained in air regarding cation adsorption, although those obtained in air at low temperatures may represent an interesting alternative.